Selv under ekstreme betingelser har man liv, finnes det også liv utenfor jorda? - Brunfelt, Arild O (Naturen, 2002)
Livets opprinnelse er et mysterium. Ikke desto mindre er mange forskere beskjeftiget med å forsøke og rekonstruere dette. Moderne forskning på livet under ekstreme betingelser på Jorda som f.eks. i dyphavet, i en innsjø under isen i Antarktis eller i en gruppe sjeldne meteoritter, har ført til en viss optimisme når det gjelder å finne liv på planeten Mars og på Jupiters månesatelliter Europa, Callisto og Ganymede.
Keywords: Antarktis; kjemiske analyser; mikrober; mikrobiologi; subglasial innsjø

Cryogenic grooves on a granite nunatak, Northern Victoria Land, Antarctica - French, Hugh; Guglielmin, Mauro (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2002)
Keywords: Antarktis; glasiologi; nunataker

Glacial history of the Antarctic Peninsula since the Last Glacial Maximum–a synthesis - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 2002)
The extent of ice, thickness and dynamics of the Last Glacial Maximum (LGM) ice sheets in the Antarctic Peninsula region, as well as the pattern of subsequent deglaciation and climate development, are not well constrained in time and space. During the LGM, ice thickened considerably and expanded towards the middle–outer submarine shelves around the Antarctic Peninsula. Deglaciation was slow, occurring mainly between >14 Ky BP (14C kilo years before present) and ca. 6 Ky BP, when interglacial climate was established in the region. After a climate optimum, peaking ca. 4 - 3 Ky BP, a cooling trend started, with expanding glaciers and ice shelves. Rapid warming during the past 50 years may be causing instability to some Antarctic Peninsula ice shelves.
Keywords: Antarktis; glasiologi; klimaendringer; marin geologi; paleoklimatologi

Typisk pingvin!: en bok fra Antarktis - Lillevik, Linda (Eide, 2002)
Keywords: Antarktis; Sørishavet; barnebøker; fugler

Klarius Mikkelsen's landing site: some further notes on the 1935 Norwegian visit to the Vestfold Hills, East Antarctica - Norman, Frederick Ian; Gibson, John A E; Jones, R T; Burgess, J S (Polar Record, 2002)
Further details regarding the landing made by Klarius Mikkelsen in the Tryne Islands, Vestfold Hills, East Antarctica, are given, being derived mainly from newspaper accounts made by Leif Sørsdal. All involved in the landing on 20 February 1935 have been identified, details of material left in the depot under the raised flag are given, and more extended information relating to the voyage to and from the site and the area generally are presented. Some comparison is made between Sørsdal's accounts and others. While the national importance of the landing was commented on, only Sørsdal apparently realised (but did not state) the insular nature of the site. Recent observations at the site suggest that its location is 68°22′38.22″S, 78°24′50.10″E, rather than that previously stated; bracing of the flagpole itself has been modified at some stage since its erection. Finally, some discussion is made regarding on-going questions relating to the accepted time on board ship, and possible consequences of errors.
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

The gastrointestinal tract of Adélie penguins – morphology and function - Olsen, Monica; Myklebust, Reidar; Kaino, Turid; Elbrønd, Vibeke; Mathiesen, Svein (Polar Biology, 2002)
Keywords: Antarktis; pingviner; zoologi

Comparison of measurements and model calculations of stratospheric bromine monoxide - Sinnhuber, Björn‐Martin; Arlander, D William; Bovensmann, H; Burrows, J P; Chipperfield, M P; Enell, Carl-Fredrick; Frieß, U; Hendrick, F; Johnston, P V; Jones, R L; Kreher, K; Mohamed-Tahrin, N; et al. (Journal of Geophysical Research: Atmospheres, 2002)
Ground-based zenith sky UV–visible measurements of stratospheric bromine monoxide (BrO) slant column densities are compared with simulations from the SLIMCAT three-dimensional chemical transport model. The observations have been obtained from a network of 11 sites, covering high and midlatitudes of both hemispheres. This data set gives for the first time a near-global picture of the distribution of stratospheric BrO from ground-based observations and is used to test our current understanding of stratospheric bromine chemistry. In order to allow a direct comparison between observations and model calculations, a radiative transfer model has been coupled to the chemical model to calculate simulated slant column densities. The model reproduces the observations in general very well. The absolute amount of the BrO slant columns is consistent with a total stratospheric bromine loading of 20 ± 4 ppt for the period 1998–2000, in agreement with previous estimates. The seasonal and latitudinal variations of BrO are well reproduced by the model. In particular, the good agreement between the observed and modeled diurnal variation provides strong evidence that the BrO-related bromine chemistry is correctly modeled. A discrepancy between observed and modeled BrO at high latitudes during events of chlorine activation can be resolved by increasing the rate constant for the reaction BrO + ClO → BrCl + O2 to the upper limit of current recommendations. However, other possible causes of the discrepancy at high latitudes cannot be ruled out.
Keywords: Antarktis; atmosfæren; fysikk; kjemiske analyser; meteorologi; miljø; målinger; polarområdene; stratosfæren

Helse på hvalfangst - Thoresen, Per (Vestfoldminne, 2002)
Keywords: Antarktis; arbeidsforhold; erindringer; helse; hvalfangere; hvalfangst; lege; medisin; pelagisk; sjøfolk; sjømenn

Body Condition and Parental Decisions in the Snow Petrel (Pagodroma nivea) - Tveraa, Torkild; Guttorm, N. Christensen (The Auk, 2002)
In Procellariiformes, parents guard the chick for some time after it has attained homeothermy. Such a strategy may have evolved to protect the chick from predation or inclement weather, but it is costly because only one parent can forage at a time. Therefore, the decision to leave the chick seems to be a trade-off between the chick's ability to care for itself, body condition of the parent present at the nest, and ability of the bird out foraging to return to the nest before its mate's body condition has degraded. We studied chick growth and survival together with number of days Snow Petrel (Pagodroma nivea) chicks were guarded before being left alone for the first time in relation to the parents body condition and ability to return to the nest in time. Parents in good body condition were more likely to produce a chick that survived the guard stage. They also guarded their chick for a longer period (range 2–8 days, x̄ = 4.5) and finally left it alone with a higher body mass than those in poor body condition. However, whether the foraging bird was able to return to the nest in time to relieve its mate was also strongly related to number of days the chick was guarded and its body mass. The chicks' survival from when they were left alone and until day 10 posthatch was positively related both to number of days they were guarded and their body condition (body mass corrected for age).
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi

Effect of isolation temperature on the characteristics of extracellular proteases produced by Antarctic bacteria - Vazquez, Susana C; Mac Cormack, Walter P (Polar Research, 2002)
Protease-producing psychrotolerant bacteria were isolated from Antarctic biotopes on casein agar plates using different incubation temperatures. Most of the isolates were non-spore-forming Gram-negative motile rods with catalase activity, 30% were pigmented and none of them were glucose fermenters. All the strains were grown in liquid cultures at 20°C and protease secretion was tested using the azocasein method. Despite their capacity for production of a clear zone of hydrolysis in agar plates, some strains did not produce detectable levels of proteolytic activity in liquid cultures. The lowest apparent optimum temperature for protease activity found in culture supernatants was 40°C. Almost all the strains showed activation energy values about 10-20 kJ-mol?1 lower than that observed for a mesophilic Subtilisin. Most of the proteases showed optimal activity at neutral or alkaline pH values and developed a multiple-band profile on gelatine-SDS-PAGE. It was observed that the lower the strain isolation temperature was, the more stongly cold-adapted–in terms of optimal temperature and activation energy–were the proteases produced by them. This dependence of the characteristics of the proteases on the isolation temperature is an important factor to take into account in the design of screening programmes directed towards the isolation of psychrotolerant bacteria able to produce proteases strongly or weakly adapted to work in the cold. The Antarctic area explored proved to be a promising source of proteolytic bacteria with potential use in industrial processes to be carried out at low or moderate temperatures.
Keywords: Antarktis; analyser; bakterier; ekspedisjoner; mikrobiologi